2002
DOI: 10.1074/jbc.m203371200
|View full text |Cite
|
Sign up to set email alerts
|

Specificities of Enzymes of Glycosylphosphatidylinositol Biosynthesis in Trypanosoma brucei and HeLa Cells

Abstract: A series of synthetic analogues of D-GlcN␣1-6-D-myoinositol-1-HPO 4 -sn-1,2-dipalmitoylglycerol, consisting of 22 variants of the D-GlcN or lipid components, were tested in trypanosomal and human (HeLa) cell-free systems. The assays measured the abilities of the analogues to act as substrates or inhibitors of the enzymes of glycosylphosphatidylinositol biosynthesis downstream of GlcNAc-phosphatidylinositol (GlcNAc-PI) de-N-acetylase. One compound, 4-deoxy-D-GlcN␣1-6-D-myo-inositol-1-HPO 4 -sn-1,2-dipalmitoylgl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…Consistent with this model, [ 3 H]GlcN labeling studies have shown that GlcN-diacyl-PIs are synthesized by L. major promastigotes (70), providing potential non-ether lipid substrates for protein GPI anchor synthesis, and cell-free GPI biosynthesis studies have suggested that the GDP-Man:Man-GlcN-PI (␣1-3) mannosyltransferase may not act on Man-GlcN-diacyl-PI (3). There are precedents for lipid specificity/selectivity for certain mammalian GPI biosynthetic enzymes, although GPI anchor synthesis in T. brucei shows a relaxed specificity for the composition of the lipid anchor (71,72). Future studies may explore the lipid specificity of LPG/GIPL and protein GPI anchor synthesis in L. major in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this model, [ 3 H]GlcN labeling studies have shown that GlcN-diacyl-PIs are synthesized by L. major promastigotes (70), providing potential non-ether lipid substrates for protein GPI anchor synthesis, and cell-free GPI biosynthesis studies have suggested that the GDP-Man:Man-GlcN-PI (␣1-3) mannosyltransferase may not act on Man-GlcN-diacyl-PI (3). There are precedents for lipid specificity/selectivity for certain mammalian GPI biosynthetic enzymes, although GPI anchor synthesis in T. brucei shows a relaxed specificity for the composition of the lipid anchor (71,72). Future studies may explore the lipid specificity of LPG/GIPL and protein GPI anchor synthesis in L. major in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the genes involved in the GPI anchor biosynthetic pathway have been cloned [14], and activities encoded by some of these genes have been characterized [15]. In contrast with the knowledge on the biosynthesis of GPI anchors, there is a complete lack of information on their degradation.…”
Section: Introductionmentioning
confidence: 99%
“…S10 in SI). The nature of the glycosidic linkages was then analysed by digestion with jack bean α-mannosidase [23], which showed that all products formed from 1 and 2 were α-linked mannosides (Figs. S11 and S12 in SI).…”
Section: Resultsmentioning
confidence: 99%